2022
DOI: 10.48193/revistamexicanadeurologa.v80i4.640
|View full text |Cite
|
Sign up to set email alerts
|

Infección de vías urinarias después de resección transuretral de vejiga: Microbiología, resistencia antibiótica y factores de riesgo asociados.

Abstract: Objective: Investigate the microbiology and incidence of drug resistance in patients undergoing TURBT and to identify independent risk factors for UTI following surgery. Material & Methods : Retrospective observational study of prospectively collected data of 199 patients who underwent TURBT in a tertiary care center in Mexico City between 2017-2019. Baseline characteristics and microbiological data (frequency of isolated bacteria and antibiotic resistance pattern) were analyzed according to the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our findings concur with those of ( 24), who reported that 73 (24%) of the 308 urine samples from cancer patients in Nebal that had been subjected to culture contained bacterial growth. (25) similarly in line with our findings, discovered that from approximately 199 bladder ca. patients in Mexico City, 20 patients (10%) had UTI following TURBT; 100 of the 497 processed samples from cancer patients in India who were thought to have UTIs tested positive for bacterial growth, according to (23); At Al-Diwaniya Teaching Hospital/Al-Diwaniya Governorate/Iraq, 33 urine samples from bladder Ca.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings concur with those of ( 24), who reported that 73 (24%) of the 308 urine samples from cancer patients in Nebal that had been subjected to culture contained bacterial growth. (25) similarly in line with our findings, discovered that from approximately 199 bladder ca. patients in Mexico City, 20 patients (10%) had UTI following TURBT; 100 of the 497 processed samples from cancer patients in India who were thought to have UTIs tested positive for bacterial growth, according to (23); At Al-Diwaniya Teaching Hospital/Al-Diwaniya Governorate/Iraq, 33 urine samples from bladder Ca.…”
Section: Discussionsupporting
confidence: 92%